Your Heart was Made for This: Contemplative Practices for Meeting a World in Crisis with Courage, Integrity, and Love - Sofer, Oren Jay (Boulder, Colorado : Shambhala, 2023)
"Meditation teacher Oren Jay Sofer shares a practical guide to developing the inner resources necessary to meet a world in crisis with a clear, balanced, and courageous outlook. Through touching stories, insightful reflections, and practical instructions, Sofer offers powerful tools to strengthen our hearts and nourish the qualities that can transform our world. In 26 chapters-each with practices to cultivate an important quality like mindfulness, wonder, balance, and empathy-you'll learn to: Have greater control of your attention Develop an inner aspiration and navigate around obstacles to fulfill it Generate positive states of mind before and during moments of stress Connect your intention to your daily activity with greater clarity Identify burnout and take action to renew yourself"--
Keywords: Meditation; Mindfulness (Psychology); Mental healing; Self-help techniques